2018
DOI: 10.3390/nano8120998
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Roll Grinding and High-Pressure Homogenization Can Prepare Stable Bicelles for Drug Delivery

Abstract: To improve the solubility of the drug nifedipine (NI), NI-encapsulated lipid-based nanoparticles (NI-LNs) have been prepared from neutral hydrogenated soybean phosphatidylcholine and negatively charged dipalmitoylphosphatidylglycerol at a molar ratio of 5/1 using by roll grinding and high-pressure homogenization. The NI-LNs exhibited high entrapment efficiency, long-term stability, and enhanced NI bioavailability. To better understand their structures, cryo transmission electron microscopy and atomic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…It is noticeable that the bicelles formulation F2 (T80) showed the best dissolution profile with the maximum % drug dissolved of 99.2 ± 2.6 % in the first 10 min, the formulation retained the supersaturation till 30 min and a slight drug precipitation was observed at 45 min to yield % dissolved of 89.6±1.6 % after 1 h. On the other hand, Labrasol ® based bicelles (F1) exhibited high yet incomplete dissolution of curcumin as the maximum % of drug dissolved was 73.1±2 % though the drug was completely soluble in the form of an isotropic solution as depicted in Fig. 2A , this may be suggesting the occurrence of a slight variation in the bicelles structure upon dilution, in accordance with a previous report that stated the occurrence of transition in the disc structure upon certain dilution conditions to larger structures such as vesicles ( 53 ). This dilution effect is not observed in T80 bicelles and that is in agreement with the literature as it has been reported that T80 bicelles exhibited resistance to dilution ( 5 ).…”
Section: Resultssupporting
confidence: 90%
“…It is noticeable that the bicelles formulation F2 (T80) showed the best dissolution profile with the maximum % drug dissolved of 99.2 ± 2.6 % in the first 10 min, the formulation retained the supersaturation till 30 min and a slight drug precipitation was observed at 45 min to yield % dissolved of 89.6±1.6 % after 1 h. On the other hand, Labrasol ® based bicelles (F1) exhibited high yet incomplete dissolution of curcumin as the maximum % of drug dissolved was 73.1±2 % though the drug was completely soluble in the form of an isotropic solution as depicted in Fig. 2A , this may be suggesting the occurrence of a slight variation in the bicelles structure upon dilution, in accordance with a previous report that stated the occurrence of transition in the disc structure upon certain dilution conditions to larger structures such as vesicles ( 53 ). This dilution effect is not observed in T80 bicelles and that is in agreement with the literature as it has been reported that T80 bicelles exhibited resistance to dilution ( 5 ).…”
Section: Resultssupporting
confidence: 90%
“…In the industrial production process of liposomes, some important technical nodes are usually involved, such as control of particle size, removal of free drugs, and removal of ethanol. , First, hydration of phospholipids generally requires industrialization by ethanol dilution. The industrialized particle size control methods mainly include high-pressure homogenization, high-pressure carbonate film extrusion, and high-pressure homogenization-combined extrusion. , These technologies make the particle sizes of liposomes smaller and more uniform. In the industrial production of liposomes, tangential flow ultrafiltration technology is often used to remove free drugs or ethanol from liposomal solutions.…”
Section: Preparation Of Liposomes and Effects Of Physicochemical Prop...mentioning
confidence: 99%
“…The industrialized particle size control methods mainly include high-pressure homogenization, high-pressure carbonate film extrusion, and high-pressure homogenization-combined extrusion. 125,126 These technologies make the particle sizes of liposomes smaller and more uniform. In the industrial production of liposomes, tangential flow ultrafiltration technology is often used to remove free drugs or ethanol from liposomal solutions.…”
Section: ■ Preparation Of Liposomes and Effects Of Physicochemical Pr...mentioning
confidence: 99%
“…However, this method could not be used to produce Nano-level preparation. On the other hand, the wet method usually uses high-pressure homogenization to form uniform nanoparticles in the presence of an organic solvent [8]. However, it is a challenge to remove residual organic solvent.…”
Section: -(2-mentioning
confidence: 99%